Factors affecting the growth of small and medium Enterprises in Luangnamtha Province - phosavath, soudakone; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study is to study the operating conditions and factors affecting the growth of small and medium enterprises in LuangNamtha Province. which uses descriptive study methods, surveys, and questionnaires to collect data from small and medium-sized enterprise operators who have registered enterprises at the Department of Industry and Trade in LuangNamtha Province according to the law in the number of 233 business units using basic statistics such as average value and standard deviation and analyzed with an ordinary least squares regression model. The results of the study found that most of the business operators are males aged between 37-43 years old, have a high degree of specialization, and have previous experience in the service sector, which a business is owned by a single Lao person. The registered capital of the business is less 100,000,000 kip, it is a source of funds for the family, there are between 5-20 people, the duration of the business operation is less 5 years, the customer group is in the province, the business is mainly in the commercial sector, but the performance is not good compared to last year. Such as, revenue and net profit decreased. The importance of factors affecting the growth of small and medium-sized enterprises in LuangNamtha province is very important. The factors affecting the growth of enterprises include four factors that have a relationship in the same direction, such as leadership factors affecting the growth of enterprises with a statistical significance level of 0.1, strategic decision-making factors affecting the growth of enterprises with a statistical significance level of 0.05, financial factors affecting the growth and stability of enterprises with a statistical significance level of 0.01 and 0.1, respectively, and marketing factors affecting the stability of the enterprise with a statistical significance level of 0.1.